Implementasi Artificial Intelligence (Ai) Dalam Meningkatkan Kreativitas Siswa Pada Sekolah Menengah Di Kota Padang - Putri Anggraini; renita astri; Zulfahmi .; faradika .; dio prima mulya; sularno .; intan utnasari (CV. ITTC INDONESIA, 2026)
The rapid development of Artificial Intelligence (AI) technology has significantly influenced various sectors, including education. However, the integration of AI in secondary school learning environments remains limited due to low digital literacy and insufficient understanding of AI applications among students and teachers. Preliminary observations conducted at MAN 3 Padang, SMA Negeri 6 Padang, and SMK Negeri 5 Padang indicated that most students were unfamiliar with the practical use of AI as a tool to support learning and creative activities. Therefore, this community service program aimed to improve students’ Artificial Intelligence literacy and enhance their creativity through training and implementation of AI-based applications in the learning process. The implementation method employed a participatory approach consisting of several stages, including needs assessment, socialization of AI concepts, training on AI creative applications such as ChatGPT and Canva AI, implementation of AI-based creative projects, and evaluation using pre-test and post-test methods. The results showed a significant improvement in students’ understanding of AI concepts, increasing from 32% before the training to 85% after the training. Furthermore, students’ ability to utilize AI tools for creative tasks increased from 20% to 82%. Participants were able to produce various digital works such as posters, short articles, and visual designs using AI-based tools. In addition, the program produced AI learning modules and established student AI communities in partner schools to ensure the sustainability of the program. This activity contributes to improving students’ digital literacy and demonstrates the potential of Artificial Intelligence integration in supporting creative and technology-based learning at the secondary school level.